Starostniki in pljučne bolezni - Mušič, Ema (Zdravniški vestnik, 2008)
The structural and functional changes of the lung and pulmonary host defenses in the elderly are presented. These facts have to be in mind in diagnostcs andmanagement of common lung diseases like asthma, COPD, pneumonia, pulmonary embolisms and pulmonary hypertension, bronchiectasis, and diffuse interstitiallung diseases. The suggestions for outpatient management, admitionto pulmonologist and to hospital are given. At discharge from hospitalclear further general procedures and drug treatment must be also givenfor the home care or nursing care. The elderly is of age > 65 years, mostly with comorbidities, thereby it must be considered in actual disease of aging lung. Given suggestions are based on our clinical evidence and the data from literature.
Keywords: Aged; Asthma; Astma; Bronchiectasis; Bronhiektazija; Hipertenzija pljučna; Hypertension, Pulmonary; Lung Diseases, Interstitial; Lung Diseases, Obstructive; Pljučna embolija; pljučne bolezni; Pljučne bolezni intersticijske; Pljučne bolezni obstruktivne; Pulmonary Embolism; Starostniki